2004
DOI: 10.1007/s11095-004-5171-6
|View full text |Cite
|
Sign up to set email alerts
|

The Mode of Drug Particle Detachment from Carrier Crystals in an Air Classifier-Based Inhaler

Abstract: A high ratio of removal forces to adhesive forces causes a high drug detachment rate from carrier crystals in a classifier within the first 0.5 s of inhalation. The high ratio can be explained by dislodgment of agglomerates and the largest primary particles in the early phases of inhalation. At higher flow rates, detached agglomerates may be further disintegrated into primary particles before they are discharged from the classifier. Agglomeration of drug particles on the carrier surface is the result of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Decreasing the size of carrier particles was shown to lead to increased [18,41,61,81,130,[140][141][142][143][144][145][146][147], decreased [135,143,144], and similar [64,80,[148][149][150][151][152][153] FPFs of drug. This is because the degree by which carrier size affects the dispersion of a DPI formulation is influenced by other interacting variables such as the type of drug [154], type of inhaler [144], the chemical nature of carrier [155], and the amounts of fine excipient additives [156].…”
Section: Size Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreasing the size of carrier particles was shown to lead to increased [18,41,61,81,130,[140][141][142][143][144][145][146][147], decreased [135,143,144], and similar [64,80,[148][149][150][151][152][153] FPFs of drug. This is because the degree by which carrier size affects the dispersion of a DPI formulation is influenced by other interacting variables such as the type of drug [154], type of inhaler [144], the chemical nature of carrier [155], and the amounts of fine excipient additives [156].…”
Section: Size Distributionmentioning
confidence: 99%
“…In another study, Young et al [142] showed that above a certain concentration, drug concentration has no further promoted aerosol performance. This can is because above a certain concentration, the discontinuities on carrier surfaces become saturated with drug particulates, and thus drug particulates become no longer protected from the press-on forces during the blending process [54,130,140,280]. This could affect the drug-drug agglomeration, drug-carrier adhesion, and drug redistribution over carrier surfaces in adhesive mixtures.…”
Section: Carrier Payload and Batch Sizementioning
confidence: 99%
“…Thus it could be seen that the forces of drug loading on to the film surface affect the aerosol characteristics of the drug dispersions. These forces are responsible for drug aggregation on the lactose carrier surface (Kulvanich and Stewart 1987;de Boer et al 2004a). This aggregation increases the magnitude of the removal forces acting on such particles during inhalation (Louey and Stewart 2002) and the degree of aggregation might affect the FPF (de Boer et al 2004a(de Boer et al , 2004bPodczeck 1998b).…”
Section: Drug Dispersionmentioning
confidence: 99%
“…These forces are responsible for drug aggregation on the lactose carrier surface (Kulvanich and Stewart 1987;de Boer et al 2004a). This aggregation increases the magnitude of the removal forces acting on such particles during inhalation (Louey and Stewart 2002) and the degree of aggregation might affect the FPF (de Boer et al 2004a(de Boer et al , 2004bPodczeck 1998b). If drug aggregation is strong enough to withstand the forces that need to break them up, the fraction detached may be high, but FPF will be unsatisfactory (Podczeck 1998b).…”
Section: Drug Dispersionmentioning
confidence: 99%
See 1 more Smart Citation